Crystal structure of bis(η2, σ1-8-methoxycyclooct-4-enyl)(μ2-1,4,8,11-tetraazacyclotetradecane-κ4 N, N′, N″, N‴)diplatinum(II) dibromide, C28H54Br2N4O2Pt2 - Ha Kwang (Zeitschrift für Kristallographie - New Crystal Structures)
C28H54Br2N4O2Pt2, monoclinic, P21/n (no. 14), a = 9.798(5) Å, b = 11.389(5) Å, c = 15.228(7) Å, β = 107.148(14)°, V = 1623.6(12) Å3, Z = 2, Rgt(F) = 0.0273, wRref(F2) = 0.0529, T = 223 K.